2012
DOI: 10.5121/ijassn.2012.2302
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Wireless Communication Using Genetic Algorithm Guided Faster Light Weight Digital Signature Algorithm (Gadsa)

Abstract: In this paper GA based light weight faster version of Digital

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In figure 14 it is observed that larger window size for doubling is needed when StorageRoom is Max. Now set the weight value equals to 0.5 for the fuzzy rules 1,5,10,13,14,15,16,18,20,21,22, 23, 25, 26 then doubling will be increase by larger window size due to the fact that StorageRoom controlled the major functions. If PreComputing and Doubling are decreased by 0.02% and StorageRoom is increased by 0.04% then the output will change.…”
Section: Number Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In figure 14 it is observed that larger window size for doubling is needed when StorageRoom is Max. Now set the weight value equals to 0.5 for the fuzzy rules 1,5,10,13,14,15,16,18,20,21,22, 23, 25, 26 then doubling will be increase by larger window size due to the fact that StorageRoom controlled the major functions. If PreComputing and Doubling are decreased by 0.02% and StorageRoom is increased by 0.04% then the output will change.…”
Section: Number Ofmentioning
confidence: 99%
“…For these reasons WSN needs faster public-key cryptographic algorithm which satisfied all these constraints [18,19,20,21]. Neal Koblitz and victor Miller was proposed Elliptic Curve Cryptography (ECC) [2].…”
Section: Introductionmentioning
confidence: 99%
“…is is generally a technology that uses the unique technology of computer to automatically analyze the information collected, observed, and obtained by sensors with different numbers obtained by the algorithm of time sequence division and cooperation under certain specific criteria. en, optimization and synthesis are carried out to complete the final decision-making algorithm and the information cooperative processing process for multitask processing [20]. According to this definition, various sensors are the basis of data fusion; for example, they can be used to construct and solve nonlinear programming problems.…”
mentioning
confidence: 99%